Development of Enterprise Architecture in XYZ Agency Using Enterprise Architecture Planning (EAP) Based on the Zachman’s Framework Approach - Supriyadi, Hari; Rahmana, Arief (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to make the design of the development of an integrated information system to support business processes that have been established in order to conform with the vision, mission and objectives to support the company.Makes the design development of integrated information systems at XYZ Agency, the framework used is Enterprise Architecture Planning (EAP) as a framework for the design of an integrated information system to assist the business process XYZ Agency, while the stages / steps, among others: the initiation of planning, Business Modeling-Technology Currently, Architectural Design Data, Technology and Applications and implementation.The findings of this study can provide guidance in the development of an integrated system to provide efficiency and effectiveness of processes between divisions as part or division one part or other divisions within the organization very well integrated.Further observations are needed in the future as a guide in further system development, this can facilitate the development of the system because the guidelines or blueprints are made according to the needs of the company.This research is expected to provide a reference in designing integrated information systems, especially the use or selection of frameworks that are in accordance with the capabilities and conditions of the company and in accordance with company needs.